How to communicate with older adults about climate change: a systematic review - Pinna, Samuele; Longo, Diego; Zanobini, Patrizio; Lorini, Chiara; Bonaccorsi, Guglielmo; Baccini, Marco; Cecchi, Francesca (Frontiers in Public Health, 2024)
Introduction Although older adults are particularly vulnerable to the effects of climate change, they seem to be overall less concerned about it, and less inclined to support climate policies. The study aims to identify the communication strategies that have been evaluated in promoting awareness and/or climate friendly behaviors in older adults. Methods We searched multiple electronic databases for studies that evaluated the effects of any interventions aimed at communicating climate change to older persons (over 65 years) and assessed the results as awareness and /or behavioural changes. We selected quantitative, qualitative and mixed methods studies, and we also included systematic reviews for cross-referencing. Risk of bias of included studies was evaluated using different tools according to the study design. Results From a total of 5486 articles, only 3 studies were included. One mixed-method study engaged older adults to assess the community vulnerability to climate change and to develop adaptation recommendations based on their perspectives; one qualitative study conducted focus groups to identify the more effective language, values and themes based on participants’ responses to narratives; one quantitative study utilized a 360-degree audio-visual platform allowing users to engage with immersive visualizations of sea-level rise scenarios. Discussion Despite the paucity of literature, this review demonstrates the potential for different strategies to increase the awareness of older persons about climate change. The involvement of older adults in the communication process, the identification of their priorities, and the integration of technology in their daily lives are promising approaches but more research, including both quantitative and qualitative studies is recommended on this topic